Concurrent In-situ formation of Ag/Ag2S nanoparticles in polymer matrix by facile polymer-inorganic solid state reaction - Waghmare, Sujata; Shinde, Manish; Gholap, Ramkrishna S.; Rao, N. Koteswara; Hawaldar, Ranjit R.; Mulik, Uttam P.; Amalnerkar, Dinesh P. (Journal of Nano Research, 2009)
We herein report the feasibility of polymer-inorganic solid-state reaction route for simultaneous in situ generation of Ag & Ag2S nanostructures in polymer network wherein an engineering thermoplastic, polyphenylene sulphide (PPS), itself acts as a chalcogen source as well as a stabilizing matrix for the resultant nanoproducts. Typical solid-state reaction was accomplished by simply heating the physical admixture of the two reactants i.e. AgNO3 and PPS by varying molar ratios mainly 1:1, 1:5, 1:15, 1:20, at the crystalline melting temperature (285 degrees C) of PPS. The synthesized nanoparticles were characterized by various physico-chemical techniques like X-ray Diffractometry, Scanning Electron Microscopy equipped with EDAX, Transmission Electron Microscopy and UV-Visible spectroscopy. The prima facie observations suggest the effective formation and subsequent entrapment of mainly nanocrystalline metallic silver (fcc) in PPS matrix for all the molar ratios chosen for the reaction. Additionally, simultaneous occurrence of nanocrystalline Ag2S (monoclinic phase) is also noticed in case of heated admixture of AgNO3: PPS with equimolar ratio. The TEM analysis reveals nanoscale polydispersity (5nm to 70nm) and prevalence of mainly spherical morphological features in all the cases with occasional indications of triangular and hexagonal morphological features depending upon the reaction molar ratio.
Keywords: Ag; Ag2S; Nanoparticles; Polymer inorganic solid -state reaction; Thermoplastic polymer matrix